Characteristics of Organic Matter and Biomarkers in Core Sediments From the Offshore Area of Leizhou Peninsula, South China Sea - Gao, Yuan; Tan, Jingqian; Xia, Jia; Wang, Yao-Ping; Wang, Sibo; Han, Yongqiang; He, Jiefeng; Song, Zhiguang (Frontiers in Earth Science, 2021)
Total organic carbon (TOC), total nitrogen (TN) and multi-biomarker indexes were analyzed for two sediment cores from the eastern coastal area of the Beibu Gulf (core 45, AMS 14C dated) and Qiongzhou Strait (core 29), South China Sea. The results showed that the TOC and TN content of the samples studied were 0.32-0.62% and 0.02-0.07%, respectively. The hydrocarbonsin offshore sediments of Leizhou Peninsula wereconsisted of biogenic hydrocarbons and petrogenic hydrocarbons. The Core 29 sediments contain higher terrigenous organic matter than that of sediments in core 45 due to the difference in hydrodynamic conditions. The composition and distribution of various lipid biomarkers indicates the presence of petrogenic hydrocarbons in the sediments of the whole profile of two sediment cores. There are multiple natural sources of hydrocarbons that could potentially contribute to the petroleum background through oil seeps and erosion of carbon-rich rock outcrops or bitumen deposits. Deep sourced hydrocarbon inputs from the submarine hydrocarbon seepage cannot be excluded. Further study is needed to resolve the specific sources for the petrogenic hydrocarbons and may be significant to petroleum exploration in the study area.